La soma-esthétique ou l’art de penser l’expérience - Barbara Formis (Appareil)
In this paper, I look back at my career as an intellectual with a view to analyzing the contribution that the practice of dance made to my philosophical and scientific research. My encounter with the thought of Richard Shusterman marked a point of renewal in my research because in his work the problem of the dualism between body and thinking is treated in a thematic and experiential way in order to underline the specificity of pragmatism and somaesthetics. I developed an interpretation of somaesthetics according to which the latter’s continuist perspective places the role of the art world and of performative artistic practice in general on the same level as that of the gestures of ordinary life.